Porphyrin–poly(arylene ether sulfone) covalently functionalized multi-walled carbon nanotubes: synthesis and enhanced broadband nonlinear optical properties. Issue 79 (9th August 2016) - Du, Yinlong; Dong, Ningning; Zhang, Menghan; Zhang, Yunhe; Luan, Jiashuang; Lu, Yaning; Zhang, Shuling; Sun, Ningwei; Wang, Jun; Wang, Guibin
Abstract : A porphyrin polymer functionalized MWNT hybrid was synthesized with enhanced NLO performance due to the synergistic effect of different mechanism and photo-induced ET/PET process. Abstract : A novel multi-walled carbon nanotube (MWNT) hybrid was synthesized by covalently attaching a porphyrinated poly(arylene ether sulfone) onto the surface of carbon nanotubes. The polymer functionalized nanotube exhibited excellent solubility in organic solvents, and the weight% of MWNTs in the resulting hybrid was found to be 36%. Considerable fluorescence quenching and shortened fluorescence lifetime were observed in the MWNT hybrid due to the photo-induced electron/energy transfer behavior from porphyrin moieties to MWNTs. Z -scan measurements demonstrated the improved broadband nonlinear optical performance of the MWNT hybrid at both 532 and 1064 nm in nanoseconds, which is attributed to the accumulation effect of nonlinear absorption and scattering, and a remarkable photo-induced electron/energy transfer process. Meanwhile, the MWNT hybrid can be homogeneously dispersed in a polymer matrix, further fabricated into a uniform film with high transparency and ultrafast optical limiting response under femtosecond laser pulses.